Assessment of WHO/INRUD core drug use indicators at public and private healthcare centres in Lahore, Pakistan: a multicentre cross-sectional study - Bhatti, Zohra; Laghari, Madeeha; Tariq, Ayesha; Sundus, Ahlam (Superior University, 2024)
Background: A key element of the pharmaceutical care plan is the appropriate use of medications. Objectives: Using the WHO/INRUD core drug use indicators, this study sought to evaluate medication usage trends at both public and private healthcare centres in the Lahore district of the Punjab province of Pakistan. Methodology: A cross-sectional and descriptive study design was adopted. For data collection, 399 prescriptions (199prescriptionsfrom public and 200 prescriptions from private healthcare facilities) were systematically sampled written from February to July 2022. To evaluate the prescription indicator, patient-care and facility-specific indicators, patients randomly selected from both public and private hospitals were examined and interviewed. For each of the WHO/INRUD indicators, we considered ideal criteria that have been published. Results: The average number of medicines prescribed each encounter was reported to be 6.26% in public hospitals and 4.14% in private hospitals among the prescribing indicators, generic medication, antibiotics, and the number of times patients received injections were prescribed, respectively, in 54%, 84%, and 89% of public hospitals and 19%, 61.7%, and 78% of private hospitals. In the public and private sectors, respectively, 71% and 97% of prescription drugs were from the list of essential drugs. The average consultation time was found to be 2.1 minutes in public hospitals and 3.2 minutes in private hospitals, while the average dispensing time was reported to be 37 seconds in public hospitals and 39 seconds in private hospitals. Of the total prescribed medicines, 84% and 97%were dispensed in public and private hospitals respectively and the percent medicine adequately labelled was 100% in both healthcare facilities. Regarding patient awareness, 69% of patients in private hospitals and 42.5% of patients in public hospitals were aware of the proper dosage, frequency, and duration of the medications that were prescribed. In terms of facility-specific data, both public and private hospitals had 100% availability of the EDL copy and 82% stock of the important medications, respectively. Conclusion: Irrational use of drugs was observed in both public and private healthcare facilities. WHO/INRUD proposed 12 key initiatives to encourage rational use of medications must be put into practice as a result of present study.